The Use of Role Play Method to Increase Students Interest in Learning English After the Implementation of Online Learning due to The Covid-19 Pandemic - Husnani Aliah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
The objective of this research was to find out the contribution of applying role play method in learning English for the students of SMP Negeri 5 Maiwa. This study tried to find a learning method that can be used to increase student interest in learning after the implementation of online learning due to the covid-19 pandemic. The research used descriptive method. It involved one group of students, which was taught English through role play method. The population was the class VIII students of SMP Negeri 5 Maiwa in first semester 2021/ 2022 academic year. The population consisted of 50 students with two classes.  The research used cluster random sampling by taking only one class as a sample namely class VIII A. The number of sample was 30 students. There are two variables in this research. It consists of independent and dependent variable. The first is the students’ interest as dependent variable and the second is role play method as independent variable. The instrument of the research was questionnaire which was given after teaching learning process in two meetings. The research found that most of the students choose strongly agree(very interested) and agree(interested) in the questionnaire related to the students’ interest in learning English through role play method.